Tiktok Media On Early Children - Br Harahap, Putri Rahmasari; Ritonga, Fitriani; Azmi, Adinda Nurfadillah; Al Karim Rambe, Rahmansyah Fadlul (Pena Cendekia Insani, 2024)
In this day and age, social media is growing rapidly which can make it easier for people to interact with one another in carrying out their daily lives. If you don't keep up with developments, someone is claimed to be clueless and out of date. The social media that is currently being used by many groups is Tiktok , including children. Tiktok is a social media that is popular and popular with the public because of its simple use and lots of interesting content. This study aims to determine the positive and negative impacts of tiktok on early childhood. This study used qualitative methods, collecting data using interviews and observation. The results of the study concluded that the negative consequences of children using the tiktok application are selfish, children become closed individuals and like to be alone, children use bad language, and children easily follow the style of adults they see in tiktok content . In addition to having a negative impact on children, tiktok also has a positive impact on those who use it without going beyond limits, such as children being able to learn independently (self-taught) and training children's memory, as well as training children's creativity.